The Surge in Indonesian Robusta Coffee Price: The Interaction of Substitute Commodity Prices and Exchange Rates on Robusta Price Behavior - Aklimawati, Lya; Dharmawan, Budi; Widhiono MZ, Imam (Indonesian Coffee and Cocoa Research Institute, 2025)
Primary commodity price trends frequently exhibit co-movement patterns, demonstrating similar fluctuations. The surge in substitute commodity prices, such as Arabica coffee and cocoa, in both Indonesian and global markets has positively impacted the increasing price of Indonesian Robusta coffee. This study explored the factors driving the surge in Indonesian Robusta coffee price, particularly the co-movement of substitute commodity prices and exchange rates, and how these elements influence Indonesian Robusta coffee price behavior. Utilizing time series data from January 1, 2019, to December 31, 2024, the research applied the ARDL-ECM approach to estimate the cointegration relationships among the variables. The results revealed that lagged Indonesian Robusta prices, world Robusta price, Indonesian Arabica price, lagged world Arabica price, London cocoa price, and the Rupiah exchange rate significantly affected Indonesian Robusta price at the 1%, 5%, and 10% significance level, both in the long and short run. Furthermore, the study identified a bidirectional causality between Indonesian Robusta coffee price and three independent variables: New York, London, and cocoa indicator prices. In contrast, Arabica prices, rubber prices, and exchange rates showed no causality with the Indonesian Robusta coffee price. The analysis also indicated that price co-movement was only reflected among related commodities, while no such relationship was found for unrelated commodities. The upward trend in world Robusta price, Indonesian Arabica price, world Arabica price, and world cocoa prices can be interpreted as indicators of a flourishing agricultural primary commodity market, which may subsequently drive up Robusta coffee prices in the domestic market.